RELATIONSHIP BETWEEN MOTIVATION AND EXTRINSIC MOTIVATION TO ICREASING ENTREPRENEURSHIP IMPLEMENTATION FROM SPP AL-FALAH GROUP AT BLOK 10 VILLAGE DOLOK MASIHUL - Maulana Majied Sumatrani Saragih; Ummul Hikmah Saragih; Rico Nur Ilham (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2021)
This study aims to determine how the influence of Intrinsic Motivation and Extrinsic Motivation on Entrepreneurial Interest in the SPP (Women's Savings and Loans) Group. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. The data analysis method in this study uses multiple linear regression analysis to obtain a comprehensive picture of the influence between the variables of Intrinsic Motivation and Extrinsic Motivation on Entrepreneurial Interest by using the SPSS 17 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, the multiple linear regression model is used. The results of hypothesis testing using multiple regression analysis and t-test indicate that: that the t-table value of the Intrinsic Motivation variable is 10,064 > the t-table value (df: 58, : 5%) of 2.0017 so it can be concluded if Intrinsic Motivation has an effect positive and significant towards Entrepreneurial Interest. Furthermore, from table 4.11 it can also be seen that the t-table value of the Extrinsic Motivation variable is 1.224 < the t-table value (df: 58, : 5%) of 2.0017 so it can be concluded that Extrinsic Motivation has no significant effect on Entrepreneurial Interest.